Intervening on Burnout in Complex Organisations – the Process of an Action Research in the Hospital - Costa, P.; Ramos, S.; Passos, A. M.; Silva, S.A.; Leite, E.S. (13th European Academy of Occupational Health Psychology Conference, 2018)
This presentation describes a specific action research case study, in an internal medicine service at a major European Hospital. The mains goals are to describe a detailed intervention with a particular methodology, and also to highlight the main obstacles faced by the research team in this process. As a result, we hope to contribute to the reflection about the challenges of implementing change in the context of health services. Health professionals are at high risk for developing burnout symptoms. Directed at reducing the organisational variables affecting professionals’ burnout, an action research was developed in a specific sector of a large hospital, with 59 doctors, 66 nurses, and 42 auxiliary professionals. Action research (AR) differs from traditional empirical research in the sense that its focus in on researching with participants and not about participants; with the acquisition of knowledge from both researchers and participants as one of its key goal. Researchers conducted 11 interviews and one focus group and 20 hours of observation. The data was analysed by two researcher, using semantic segmentation of the corpus and a thematic analysis was performed (e.g., Braun & Clarke, 2006). The professionals describe the sector as technically excellent. In general, interpersonal relationships within professional groups are good, particularly within the nurses and young professionals (mostly interns and medical students). One of the most positive aspects of the sector is its potential in terms of scientific production (patients with complex situations and multiple pathologies) and teaching. However, data analysis also allowed to identify some issues considered as obstacles to effective functioning by the professionals. Professionals report demotivation and the need to address the emotional part of their job. Following the previous data systematisation, the project team defined three critical areas of intervention, each with specific broad suggestions: work organisation, teamwork and wellbeing. Nonetheless, the hierarchy blocked the proposed intervention possibilities. Organisational factors are unequivocally relevant, particularly in complex settings with emotionally charged interactions and the direct hierarchy is pivotal for facilitating organisational change. The direct hierarchy has a critical role in facilitating (or obstructing) organisational change and the consequent positive (or negative) spirals. Therefore, attempting to intervene directly with health professionals requires extra care in engaging the leadership and in making sure their intentions are aligned with the degree of change necessary to improve not only the quality of the care but also the wellbeing of professionals.